Prevalence and Patterns of Thyroid Disorders Assessed from Neck Ultrasonography in Western Nepal - Upadhyaya, Tirtha; Parajuly, SS; Pangeni, R (Journal of Gandaki Medical College-Nepal, 2018)
Background: Thyroid problems are rapidly increasing in the world. Thyroid ultrasonography may be a very simple tool to assess and screen thyroid problems. This retrospective study to assess the prevalence of thyroid disorders from neck ultrasonography in relation to age, gender and disease type was performed in Diabetes Thyroid and Endocrinology Care Center, Pokhara Nepal.Methods: Five hundred computer saved datas from the Radiology Department of Diabetes Thyroid & Endocrinology Care Center from April 2017 to April 2018 were collected. Cases were reviewed for age, gender and disease type and statistical analysis was done using SPSS tool.Results: Out of 500 patients 14% were males, 86% were females; age ranged from three days to 86 years. Hasimoto's thyoiditis was commonest problem and very prevalent in women.Conclusions: Thyroid problems are so common in general population, especially in females. Simple diagnostic tool like neck ultrasonography gives clue to make clinical diagnosis.